Reconstruction strategies for extensive bone defects following resection of primary malignant tumors in the distal radius - Guo, Qing-He; Wang, Wei; Yang, Zheng-Ming; Qiu, Yun-Jing; Wu, Jia-Dan; Wang, Ke-Yi; Tao, Hui-Min; Ye, Zhao-Ming (Frontiers in Oncology, 2025)
BackgroundThis study aimed to evaluate surgical resection techniques for primary malignant tumors of the distal radius and to examine the reconstruction strategies employed for resulting large bone defects.MethodsA retrospective analysis was conducted on 11 cases involving the resection and reconstruction of primary malignant tumors in the distal radius. Complete medical records and follow-up data from December 2013 to December 2022 were reviewed. Oncological outcomes were assessed, with specific focus on the extent of tumor invasion, surgical resection techniques, and reconstruction strategies.ResultsThe follow-up period ranged from 5 to 118 months, with a mean duration of 41.6 months. At the final follow-up, local recurrence was observed in three patients, six died due to disease progression, and five were alive. For tumors confined to the distal radius, resection of the distal radius follow by joint-preserving reconstruction using either autologous fibular grafts or 3D-printed prostheses. For tumors involving the distal radius, proximal carpal bones, and/or distal ulna, wrist arthrodesis are chose using either autologous fibular grafts or ipsilateral ulnar transposition with arthrodesis For tumors involving more than half of the distal radius, reconstruction strategies include ulnar-only fixation or wrist arthrodesis with ipsilateral ulnar transposition.ConclusionsPrimary malignant tumors of the distal radius are rare and associated with a poor prognosis. Selection of resection and reconstruction techniques is primarily influenced by the extent of tumor invasion, with joint-preserving strategies feasible in selected cases and arthrodesis required for more extensive bone involvement.